Accessible Housing in Canada: An overview of policy initiatives and the need for renewed action - Gamey, John; Terashima, Mikiko (Canadian Planning and Policy / Aménagement et politique au Canada)

(untitled) (Association of Canadian University Planning Programs, 2023)
Currently there is limited research on accessible housing provisions for persons with disabilities (PWD) within Canada. The aim of our study is to provide an overview of how shortages of accessible housing are being addressed through the National Housing Strategy (NHS), with an additional look at provincial-level initiatives to tackle the issue, using Nova Scotia as a case study. As the NHS is only five years old, a thorough overview of its outcomes was not possible. However, our study revealed a few critical shortcomings regarding current initiatives—including ambiguous targeting for accessible housing development, lack of coordination between the housing and social services sectors, and (over-)reliance on market-based solutions. Broader understanding of accessible housing needs, more empirical examples of how different sectors can work together, and clarification of the costs and benefits of accessible housing are all necessary in order to more holistically address the accessible housing challenges. Wider application of accessibility design codes, alliance-building among vulnerable community groups to develop stronger voices, and enhanced monitoring systems are additional avenues for action.